Analysing elite European basketball players` performances according to travel demands, game schedule and contextual factors - Sansone, P.; Conte, D.; Gasperi, L.; Scanlan, A. T.; Gomez-Ruano, M. A. (International Journal of Performance Analysis in Sport, 2025)
This study evaluated the effects of travel demands, scheduling, and contextual factors on individual player performances in the top 10 European basketball teams across the 2020-2021 season. Game-related statistics were analysed (n = 8,824 observations). Players were categorized into high, medium, and low status according to their average playing times. Hierarchical regression models evaluated the effects of distance travelled, hours since the previous game, contextual factors for the prior and current game, and playing position on performance indicators. Medium-status players collected fewer defensive rebounds (p = 0.009) and committed fewer fouls (p = 0.026), with more time between games. Further travelled distances were associated with reduced defensive rebounds (p = 0.017), alongside increased turnovers (p = 0.038) and 3-point shooting percentage (p = 0.032) in high-status players. After facing higher-level teams, high- and low-status players` shooting worsened (p<0.05). Guards excelled in free-throw shooting and assists, forwards had fewer turnovers, and centers had better 2-point shooting and rebounds.